Barriers Impeding the Adoption of Information and Communication Technology (ICT) in Construction Project Management - Sahamir, Shaza Rina; Ismail, Noor Akmal Adillah; Raja Muhammad Rooshdi, Raja Rafidah; Zainordin, Zainab Mohmad (International Journal of Integrated Engineering, 2021)
In today’s world, Information and Communication Technology (ICT) adoption is one of the most critical factors influencing project stakeholders’ ability to effectively coordinate and collaborate construction activities. The construction industry and its stakeholders are often confronted with a large volume of data and serious communication. Unlike other sectors, the building industry’s use of ICT has not been extensively studied. Consequently, it adds to a range of obstacles to completely using ICT. As a result, the study aimed to investigate the barriers of ICT in managing construction project. The objectives for this study were to identify the current state of ICT use in the construction industry and to investigate the barriers to ICT use in construction project management. The data for this analysis was gathered using both secondary and primary data collection methods. Secondary data was gathered using a literature review of previous studies and documents on ICT for construction project management. The study used a quantitative research design that included a questionnaire survey. To explain the respondents, a non-probability sampling approach was used. A total of 40 people responded to the questionnaire survey, which included members of different project teams. Statistical Program for Social Sciences applications was used to complete the data analysis (IBM SPSS). The results were produced using critical and descriptive analysis. Computers and email were found to be among the most widely used ICT methods for managing construction projects, according to the findings. One barrier to ICT implementation in construction project management was resistance to reform and the high cost of ICT adoption. Resistance to change and the high cost of ICT adoption were among the challenges to ICT implementation in construction project management.